Problematics of Simple Evidence Regulations for Addendums to Sales and Purchase Agreements in Pkpu Applications that are Not Based on Justice Values - Mahardika, Yekti (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Bankruptcy Law and Suspension Obligation Debt Payment (PKPU) in Indonesia adopts principle proof simple as instrument main For ensure a fast, efficient and certain judicial process law. This principle requires fulfillment element the presence of two or more creditors and debts that have been due and can billed. However, in practice justice commerce, implementation proof simple often done in a way formalistic and neglectful complexity connection the law of the parties, in particular when agreement sell buy has experience change through addendum. In fact, in law contract, addendum is the part that is not inseparable from agreement principal and have strength the same law after agreed upon by the parties. Research This aim For analyze regulations proof simple in PKPU submission based on addendum agreement sell buy, and evaluate to what extent the regulations and their implementation has reflect mark justice. The research method used is approach juridical normative empirical with type study qualitative. Data obtained through studies literature to regulation legislation, doctrine, and decisions court, as well as studies field through interviews. Data analysis was carried out use analysis content with the interactive model of Miles and Huberman for identify pattern implementation laws and inconsistencies decision. Research results show that regulations proof simple in PKPU not yet give guidelines clear normative about position addendum as fact law. As a result, judges have room broad and tending discretion put forward efficiency procedural compared to justice substantive. Inconsistency decision court commerce in assessing the addendum shows weakness certainty law and imbalance protection between creditors and debtors. Research This conclude that without reformulation regulations and standards implementation proof simple, basic the potential Keep going reproduce injustice in PKPU practices.